2021
DOI: 10.1371/journal.pone.0258687
|View full text |Cite
|
Sign up to set email alerts
|

Communicating social responsibilities through CSR reports: Comparative study of top European and Asia-Pacific airlines

Abstract: Recently the outbreak of major social incidents has put the airline industry in the forefront of the debate. However, studies related to the social dimension of the Global Reporting Initiative (GRI) Standards in aviation are limited. To fill the gap, this study explored the social themes of corporate social responsibility (CSR) practices between European and Asia-Pacific based airlines. Quantitative content analysis is employed for comparing the social topics in CSR reports of 20 top airlines from Asia-Pacific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Also, little research is provided regarding a comparative assessment of the scope of the reported content. Yang et al (2020), as well as Zhang (2021), focus on comparative studies between European airlines and air carriers from the Asia-Pacific region, while there is no systematic intra-European comparison yet, which would also take different business models into account.…”
Section: Sustainability (Reporting) and Aviationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, little research is provided regarding a comparative assessment of the scope of the reported content. Yang et al (2020), as well as Zhang (2021), focus on comparative studies between European airlines and air carriers from the Asia-Pacific region, while there is no systematic intra-European comparison yet, which would also take different business models into account.…”
Section: Sustainability (Reporting) and Aviationmentioning
confidence: 99%
“…For the airline sector, the literature body contains research providing a broad overview of reporting practices on a global level (Johansson 2022), as well as work focusing on reporting trends and their influencing factors (Kilic et al 2019). However, little research is provided regarding a comparative assessment of the scope of the reported content: Yang et al (2020), as well as Zhang (2021), conducted comparative studies between European airlines and air carriers from the Asia-Pacific region, while there is no systematic intra-European comparison yet, which would also take a closer look at different business models and related differences in reporting behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, statistical analyses have demonstrated that the firm size is likely to increase the implementation of GRI (Karaman et al, 2018) and that aviation companies based in countries with a strong governance structure and high social and environmental standards are more likely to engage in such reporting (Kılıç et al, 2019). Additionally, recent quantitative content analyses have contributed to our understanding of the development and scope of environmental, social and economic disclosure in airlines' GRIbased reporting (Yang et al, 2020;Zhang, 2021).…”
Section: Introductionmentioning
confidence: 99%